Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s00775-018-1603-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heme c attachment on heme conformation and potential

Abstract: Heme c is characterized by its covalent attachment to a polypeptide. The attachment is typically to a CXXCH motif in which the two Cys form thioether bonds with the heme, "X" can be any amino acid other than Cys, and the His serves as a heme axial ligand. Some cytochromes c, however, contain heme attachment motifs with three or four intervening residues in a CXCH or CXCH motif. Here, the impacts of these variations in the heme attachment motif on heme ruffling and electronic structure are investigated by spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…Band splitting and induction of rotational strength also require the loss of the D 4 h symmetry of the core of the porphyrin ring system. , Work on heme microperoxidases shows that the ruffling of the heme, caused by the CXXCH heme attachment sequence, is sufficient to break the D 4 h symmetry of the heme, leading to a strong CD signal in the Soret region even in the absence of the possibility of coupling to aromatic residues . Mutational studies of proteins with a c type heme show that the degree of ruffling is influenced by both the CXXCH sequence and residues that pack against this sequence. ,, The CLQCH heme attachment sequence of yeast iso-1-Cyt c differs from those of horse (CAQCH) and human (CSQH) Cyt c by having a larger residue in the second position. Perhaps this difference affects the degree of distortion from D 4 h symmetry as the structure around the heme is perturbed upon membrane binding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Band splitting and induction of rotational strength also require the loss of the D 4 h symmetry of the core of the porphyrin ring system. , Work on heme microperoxidases shows that the ruffling of the heme, caused by the CXXCH heme attachment sequence, is sufficient to break the D 4 h symmetry of the heme, leading to a strong CD signal in the Soret region even in the absence of the possibility of coupling to aromatic residues . Mutational studies of proteins with a c type heme show that the degree of ruffling is influenced by both the CXXCH sequence and residues that pack against this sequence. ,, The CLQCH heme attachment sequence of yeast iso-1-Cyt c differs from those of horse (CAQCH) and human (CSQH) Cyt c by having a larger residue in the second position. Perhaps this difference affects the degree of distortion from D 4 h symmetry as the structure around the heme is perturbed upon membrane binding.…”
Section: Discussionmentioning
confidence: 99%
“…72 Mutational studies of proteins with a c type heme show that the degree of ruffling is influenced by both the CXXCH sequence and residues that pack against this sequence. 71,73,74 The CLQCH heme attachment sequence of yeast iso-1-Cytc differs from those of horse (CAQCH) and human (CSQH) Cytc by having a larger residue in the second position. Perhaps this difference affects the degree of distortion from D 4h symmetry as the structure around the heme is perturbed upon membrane binding.…”
Section: Biochemistrymentioning
confidence: 99%
“…Turning to heme enzymes, Wilks and co-authors [15] report that disruption of an aspartic acid/arginine salt bridge in HemO, the heme oxygenase from Pseudomonas aeruginosa, leads to complete loss of enzymic activity. Bren, Elliott and co-authors [16] report on the heme ruffling and electronic structure in covalently attached heme in different motifs, for example, with three of four intervening residues, as in CX 3 CH or CX 4 CH, in variants of Hydrogenobacter thermophilus cytochrome c552. Sono, Dawson and coauthors [17] report spectroscopic evidence for the coordination of neutral thiol to Fe(II)-heme.…”
Section: Metalloproteinsmentioning
confidence: 99%
“…It has been shown that ruffling, the perturbation of the heme from perfect D 4 h symmetry, is influenced by the CXXCH heme attachment sequence and the residues that pack against this sequence. Breaking of this symmetry leads to a strong circular dichroism (CD) signal in the Soret region . The amplitude of the B-band couplet in the Soret CD is dependent on both the splitting of the band and the rotational strength .…”
Section: Resultsmentioning
confidence: 99%